Integrating Religious Moderation and Local Cultural Preservation: The Synergy of Islamic Education and Sufism at Pesantren Tebuireng - Jasminto, Jasminto (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This article discusses the importance of integrating religious moderation and the preservation of local culture in the context of Pesantren Tebuireng. Through an approach that combines Islamic education and Sufi values, this article reveals how the synergy between the two can shape a more moderate understanding of religion while simultaneously preserving and nurturing local cultural richness. The article explains how Pesantren Tebuireng, as an Islamic educational institution, has successfully harmonized the practice of religious moderation with the preservation of local cultural values through the teachings of Sufism. Using literature analysis and case studies, we identify how this integration influences the understanding of religion and supports the preservation of local culture. The research results indicate that this approach helps shape individuals who practice religion in a moderate way while promoting the preservation of a rich local culture. The integration of Islamic education and Sufi teachings paves the way for improved interfaith dialogue and understanding. This article provides insights into how these practices can be applied in other locations to achieve harmony between religion and culture.